Prospective bride interpersonal communication Judging from the Gender: Are there any differences? - Alfina Sari; Herman Nirwana; Afdal Afdal (Jurnal Aplikasi IPTEK Indonesia, 2020)
Based on the existing phenomena, there are still many brides who have not been able to establish good interpersonal communication. If the condition is ignored, it will have an impact on divorce. This research uses a quantitative descriptive approach . The population of the study was the candidate pair of pengatin in Padang City with a total sample of 43 pairs . The sampling technique used was cluster random sampling with data collection tools used in the form of Interpersonal Communication Scale (SKI) . Data were analyzed using descriptive statistics and for analysis of interpersonal communication differences based on gender brides do different test method t-test using SPSS version 22. The findings of the study revealed that interpersonal communication is in the category bride lace h with the achievements of the percentage of 44.0% , interpersonal communication on the verbal aspect is in the medium category with 45.3% percentage achievements, interpersonal communication on the nonverbal aspect is in the low category with a percentage of 37.2%. Meanwhile, the level of interpersonal communication of the bride and groom if calculated on average, men are lower than women, with 54.46 achievements and 55.81 women. However, statistically there is no significant difference between the bride and groom's interpersonal communication skills with the bride , in other words there is no significant difference in the bride's interpersonal communication skills in terms of gender . The findings of this research can then be an important need study to create interpersonal communication modules in the family for the bride and groom, so that the bride and groom understand good communication within the family and then be able to apply it.